Oceanographic and eustatic control of carbonate platform evolution and sequence stratigraphy on the Cretaceous (Valanginian–Campanian) passive margin, northern Gulf of Mexico. Issue 2 (19th September 2013) - Phelps, Ryan M.; Kerans, Charles; Loucks, Robert G.; Da Gama, Rui O.B.P.; Jeremiah, Jason; Hull, David; Eberli, Gregor
Abstract An integrated sequence stratigraphic study based on outcrop, core and wireline log data documents the combined impact of Cretaceous eustacy and oceanic anoxic events on carbonate shelf morphology and facies distributions in the northern Gulf of Mexico. The diverse facies and abundant data of the Comanche platform serve as a nearly complete global reference section and provide a sensitive record of external processes affecting Cretaceous platform development. Regional cross‐sections across the shoreline to shelf‐margin profile provide a detailed record of mixed carbonate–siliciclastic strata for the Hauterivian to lower Campanian stages (ca 136 to 80 Ma). The study window on the slowly subsiding passive margin allows the stratigraphic response to external forcing mechanisms to be isolated from regional structural processes. Three second‐order supersequences comprised of eight composite sequences are recognized in the Valanginian–Barremian, the Aptian–Albian and the Cenomanian–Campanian. The Valanginian–Barremian supersequence transitioned from a siliciclastic ramp to carbonate rimmed shelf and is a product of glacial ice accumulation and melting, as well as variable rates of mid‐ocean ridge volcanism. The Aptian–Albian supersequence chronicles the drowning and recovery of the platform surrounding oceanic anoxic events 1a and 1b. The Cenomanian–Campanian supersequence similarly documents shelf drowning following oceanic anoxic event 1d, after which the platform evolved to a deep‐subtidal system consisting of anoxic/dysoxic shale and chalk in the time surrounding oceanic anoxic event 2. Each period of oceanic anoxia is associated with composite sequence maximum flooding, termination of carbonate shelf sedimentation and deposition of condensed shale units in distally steepened ramp profiles. Composite sequences unaffected by oceanic anoxic events consist of aggradational to progradational shelves with an abundance of grain‐dominated facies and shallow‐subtidal to intertidal environments. Because they are products of eustacy and global oceanographic processes, the three supersequences and most composite sequences defined in the south Texas passive margin are recognizable in other carbonate platforms and published eustatic sea‐level curves.